Profile of Mathematical Creative Thinking in Solving Number Pattern Problems of Grade VIII Students of SMPN 15 Palu Reviewed from the Student's Self-Efficacy - Yusrayudin; Dr. Pathuddin, S.Pd., M.Si; Dr. Rita Lefrida, S.Pd., M.Si (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This qualitative research aims to obtain a description of the Profile of Mathematical Creative Thinking in Solving Number Pattern Problems of Grade VIII Students of SMP Negeri 15 Palu Reviewed from Student Self-Efficacy. The subjects of this study were one student who had high Self-Efficacy and one student who had Low Self-Efficacy. The instrument in this study was the researcher himself assisted by a Self-Efficacy Questionnaire, a mathematical problem-solving test and an interview guide. The data analysis techniques used included data condensation, data presentation, and conclusion drawing. The results of the study showed that subjects with High and Low Self-Efficacy at the stage of understanding the problem showed that the subjects fulfilled two indicators of creative thinking, namely the indicators of fluency and novelty. The stage of preparing a problem-solving plan showed that subjects with High Self-Efficacy fulfilled all three indicators of creative thinking, namely the indicators of fluency, flexibility and novelty, while subjects with Low Self-Efficacy only fulfilled two indicators of creative thinking, namely the indicators of Fluency and Flexibility. The stage of implementing the problem-solving plan shows that subjects with High and Low Self-Efficacy fulfill the three indicators of creative thinking, namely the indicators of fluency, flexibility, and novelty. The re-examination stage shows that subjects with High Self-Efficacy fulfill two indicators of creative thinking, namely the indicators of fluency and novelty. Subjects with Low Self-Efficacy also fulfill two indicators of creative thinking, namely fluency and flexibility.